Improving vaccination uptake in pediatric Cochlear implant recipients - Lisa Jin; Paula Téllez; Ruth Chia; Daphne Lu; Neil K. Chadha; Julie Pauwels; Simon Dobson; Hazim Al Eid; Frederick K. Kozak (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background An Infectious Disease vaccine specialist joined our institution’s Cochlear Implant Team in 2010 in order to address the high percentage of non-compliance to immunization prior to surgery identified previously from an internal review. The purpose of this study was to (1) review the immunization status of cochlear implant recipients in 2010–2014, (2) assess if introducing a vaccine specialist made a significant change in vaccination compliance and (3) elucidate any barriers to vaccination compliance. Methods Retrospective chart review and a telephone survey. Medical records of 116 cochlear implant recipients between 2010 and 2014 were reviewed. A telephone survey was conducted to obtain the current vaccination status in children who required post-operative vaccinations with incomplete records on chart review and, if applicable, the reason for non-compliance. Results Between 2010 and 2014, 98% of children were up-to-date at the time of surgery, compared to 67% up-to-date at the time of surgery between 2002 and 2007. 27 children were included in our post-operative immunization analysis. 29.6% (8/27) failed to receive necessary vaccinations post-surgery. Pneumovax-23, a vaccine for high-risk patients (such as cochlear implant candidates) was missed in all cases. Conclusion Pre-operative vaccination for cochlear implant recipients improved dramatically with the addition of a vaccine specialist. However, a significant proportion of patients requiring vaccinations post-surgery did not receive them. The main reason for non-compliance was due to parents being unaware that their children required this vaccine postoperatively by being “high-risk”. Although improvement was demonstrated, a communication gap continued to impede the adequacy of vaccination uptake in pediatric cochlear implant recipients following surgery at age 2 when the high-risk vaccine was due.